2004
DOI: 10.2116/analsci.20.415
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metal Ions in Coordinating Solvent Mixtures by Means of Raman Spectroscopy

Abstract: Neat DMF and DMA show the in-plane bending δ(O=C-N) vibration at 660 cm -1 and the symmetric stretching ν(N-CH3) vibration at 740 cm -1 , respectively. The metal(II) perchlorate solution usually shows a shoulder band at a higher frequency region of the free solvent band, which is ascribed to the bound Titration Raman spectroscopy has been developed for studying the solvation structure of metal ions in solution. The method affords us the solvation number, and the value thus obtained in neat solvents is in good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Neat ZnQ complex thus confers extra degrees of freedom to the coordinated bis‐8‐hydroxyquinoline (8HQ) aromatic moieties around the Zn 2+ center of the guest emitter; this effect is illustrated in the inset of Figure e. In contrast, because Zn metal centers strongly prefer DMF over DMA, coordinated DMF helps to stabilize the ZnQ structure. This is in agreement with the absorption data of ZnQ DMF @OX‐1 nanosheets, where λ max was pinpointed at 387 nm indicating that the ZnQ has coordinated DMF.…”
Section: Methodsmentioning
confidence: 99%
“…Neat ZnQ complex thus confers extra degrees of freedom to the coordinated bis‐8‐hydroxyquinoline (8HQ) aromatic moieties around the Zn 2+ center of the guest emitter; this effect is illustrated in the inset of Figure e. In contrast, because Zn metal centers strongly prefer DMF over DMA, coordinated DMF helps to stabilize the ZnQ structure. This is in agreement with the absorption data of ZnQ DMF @OX‐1 nanosheets, where λ max was pinpointed at 387 nm indicating that the ZnQ has coordinated DMF.…”
Section: Methodsmentioning
confidence: 99%
“…Complexation of ions is usually more suppressed in a solvent with a high electron-pair donating ability (Burger, 1983;Gutman, 1978). However, this does not apply to solvents with a bulky functional group in the vicinity of the coordinating atom (e.g., in a mixture of DMF + TMU, lanthanide (III) ion preferentially bind to DMF), and complexation is usually enhanced as a result of the solvation steric effects that originate from steric repulsion between solvent molecules simultaneously binding to the ion (Ishiguro et al, 2004;Umebayashi et al, 2005).…”
Section: Preferential Solvationmentioning
confidence: 99%
“…Structural parameters such as ion-ligand atom distances are required in modeling contaminant behavior and transport in mixed-solvent-soil systems. Individual and total solvation numbers can give valuable information on the solvation steric effects on the preferential solvation of ions in solvent mixtures (Ishiguro et al, 2004).…”
Section: Solvation Structurementioning
confidence: 99%
See 1 more Smart Citation
“…We have so far reported the solvation and complexation of metal(II) ions in some aprotic amide solvents, as well as in their mixtures, in view of the solvation steric effect. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Persson and co-workers reported the solvation thermodynamics of some monovalent ions in N,N-dimethylpropyleneurea (DMPU) 21 and the solvation structure and harogeno complexation of the nickel(II) ion in DMPU 22 and in the crystalline state. 23 Funahashi and Inada et al reported that the solvation number of the Co 2+ ion is 4 in 1,1,3,3-tetramethylurea and its nitromethane mixtures.…”
Section: Introductionmentioning
confidence: 99%